Genome Sequence of Bacillus subtilis subsp. subtilis Strain IITK SM1, Isolated from Kitchen Waste Compost - Prem Anand, Murugan; Hariharan, V. Chinnasamy; Shankar, Hari; Singh, Abhas; Saravanan, Matheshwaran (Microbiology resource announcements, 2019)
We report here the complete genome sequence of Bacillus subtilis subsp. subtilis strain IITK SM1, isolated from kitchen waste compost. We report here the complete genome sequence of Bacillus subtilis subsp. subtilis strain IITK SM1, isolated from kitchen waste compost. We have sequenced the whole genome of this strain to identify and characterize the enzymes that participate in efficient composting activity.